2021
DOI: 10.1186/s12957-021-02241-2
|View full text |Cite
|
Sign up to set email alerts
|

Salpingo-oophorectomy versus cystectomy in patients with borderline ovarian tumors: a systemic review and meta-analysis on postoperative recurrence and fertility

Abstract: Background To compare the postoperative recurrence and fertility in patients with borderline ovarian tumors (BOTs) who underwent different surgical procedures: salpingo-oophorectomy versus cystectomy. Methods Potentially relevant literature from inception to Nov. 06, 2020, were retrieved in databases including Cochrane Library, EMBASE (Ovid), and MEDLINE (Pubmed). We applied the keywords “fertility-sparing surgery,” or “conservative surgery,” or “c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…However, recurrence rates are elevated subsequent to UC in comparison to USO in our results, especially in the subgroup of MBOTs ( p < 0.05). A meta-analysis confirmed that cystectomy was associated with a higher recurrence rate of BOTs but no impact on the postoperative pregnancy rate [ 30 ]. MBOTs tend to be large and unilateral and contain multiple cystic spaces of varying sizes which may increase surgical difficulty and the risk of intraoperative rupture.…”
Section: Discussionmentioning
confidence: 99%
“…However, recurrence rates are elevated subsequent to UC in comparison to USO in our results, especially in the subgroup of MBOTs ( p < 0.05). A meta-analysis confirmed that cystectomy was associated with a higher recurrence rate of BOTs but no impact on the postoperative pregnancy rate [ 30 ]. MBOTs tend to be large and unilateral and contain multiple cystic spaces of varying sizes which may increase surgical difficulty and the risk of intraoperative rupture.…”
Section: Discussionmentioning
confidence: 99%
“…En cuanto al manejo quirúrgico, la cirugía preservadora de fertilidad consiste en realizar salpingooforectomía unilateral o cistectomía en estadios tempranos del tumor 18 , sin embargo existe controversia en cuanto al manejo adecuado, pues se ha descrito que la cistectomía aumenta la recurrencia del tumor aproximadamente a un 33.5% a 10 años, mientras que con la cirugía radical la recurrencia es del 12%. No se ha mostrado diferencia en la tasa de embarazo entre estos dos procedimientos 19 .…”
Section: Discussionunclassified
“…1 Cystectomy and salpingo-ophorectomy belong to Fertility-Sparing Treatment (FST). 14 Thus, this type of surgery is chosen as one of endometrioma treatment. However, surgical procedure still effects ovarian reserve, though there still a chance of pregnancy.…”
Section: Discussionmentioning
confidence: 99%